Enhancement of power quality using microprocessor based shunt active power filter for unbalanced load - Madhu B. R.; Dinesh M. N.; Tsewang Thinlas; Deril Menezes (International Journal of Electrical and Computer Engineering (IJECE), 2020)
Power quality is the most significant factor of power sector. The end user equipment such as induction motor, inverters, rectifiers inject harmonics into power system that influences the quality of power delivered. The presence of harmonics forces the use of instantaneous reactive power theory to calculate instantaneous power that helps in finding the compensating currents to eliminate harmonics. The control action required by active filter is accomplished by STM32F303RET6 microcontroller. Single phase induction motor is used as a dynamic nonlinear load in one of the three phases and resistive loads on the other two phases. TRIAC based RC triggering circuit was used to control the single phase induction motor. This paper presents the simulation and hardware implementation of shunt active power filter for 3 phase 4 wire unbalanced system. The hardware results show that THD in the source side has been reduced from 50.7% to 9.6% by implementing the SAPF.